e-Learning at Universiti Malaya: Determinants of satisfaction of use among engineering students / Effariza Hanafi ... [et al.] - Hanafi, Effariza; Khairuddin, Anis S.; Zain, Farah M.; Hassan, Zahiruddin F.A; Sulaiman, Abd Halim (UiTM Press, 2017)
This study was conducted to investigate the variables associated with satisfaction of use of the SPeCTRUM e-learning platform of Universiti Malaya among engineering students. Two domains were investigated, namely, student characteristics (computer attitude, perceived usefulness and computer self-efficacy and system characteristics (system functionality, infrastructure and technical support). A questionnaire, specially developed using items adopted from previous related studies, was used to elicit responses. Item-structure analysis of the questionnaire revealed high reliability. The sample was 70 engineering students of Universiti Malaya. The findings revealed that system functionality (β=0.649).